2019
DOI: 10.3390/ijerph17010251
|View full text |Cite
|
Sign up to set email alerts
|

Differences between WHO Growth Standards and China Growth Standards in Assessing the Nutritional Status of Children Aged 0–36 Months Old

Abstract: Background: At present, whether to use the World Health Organization’s (WHO) growth standards or native growth standards to assess the nutritional status in a given population is unclear. This study aimed to compare the differences between the WHO’s growth standards and China’s growth standards in assessing the nutritional status of children aged 0~36 months. Methods: We used z-scores to evaluate the nutritional status of children. The weight-for-age z-scores (WAZs), length/height-for-age z-scores (LAZ/HAZs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“… 5 A Chinese study that used the WHO-GCS reported the WAZ ranged from +0.1 to +0.7, and that the LAZ/HAZ also ranged from +0.1 to +0.7. 3 In addition, children from Norway (range of LAZ/HAZ: 0–1, range of WAZ: 0.1–0.9) and Greenland (range of LAZ/HAZ: 0–1.3, range of WAZ: 0.7–0.9) were generally taller and heavier than the WHO-GCS standard. 4 8 Our findings thus emphasize the need to establish national reference charts based on actual measurements of Korean BF infants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 5 A Chinese study that used the WHO-GCS reported the WAZ ranged from +0.1 to +0.7, and that the LAZ/HAZ also ranged from +0.1 to +0.7. 3 In addition, children from Norway (range of LAZ/HAZ: 0–1, range of WAZ: 0.1–0.9) and Greenland (range of LAZ/HAZ: 0–1.3, range of WAZ: 0.7–0.9) were generally taller and heavier than the WHO-GCS standard. 4 8 Our findings thus emphasize the need to establish national reference charts based on actual measurements of Korean BF infants.…”
Section: Discussionmentioning
confidence: 97%
“… 2 However, several countries reported considerable discrepancies between the WHO-CGS and their own national anthropometric data. 3 4 5 6 7 8 9 …”
Section: Introductionmentioning
confidence: 99%
“…The WHO growth standards for children from 6 to 59 months old are a useful tool for nutritional assessment and have been adopted universally for this purpose in the field of humanitarian aid. However, some systematic reviews and other studies (Hruschka, 2020; Tian et al, 2020) have highlighted notable differences between WHO standards and national or regional references obtained with the same inclusion criteria (Natale & Rajagopalan, 2014). The lack of diagnostic agreement is evident and, in addition, the WHO itself warns that the proportion of children who in successive studies, are below the limits of normality (±2 SD of the WHO standards), correspond more frequently to Asiatic populations (Ahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should include longitudinal data, to track the growth of the same children within a certain time period. Moreover, since there is no consensus on specific methodology for the comparison of growth charts between different countries or populations (some studies use paired t ‐tests, others independent sample t ‐tests, others ANCOVAS and binary logistic regressions while some use differences between z ‐scores or between mean values) (Kløvgaard et al, 2018; Nielsen et al, 2010; Park et al, 2017; Tian et al, 2020; Yang et al, 2015), we used one of the many methods found in the literature. Not having a standardized methodology prevents the possibility of comparing different studies whose research focuses on the same area.…”
Section: Discussionmentioning
confidence: 99%
“…Some countries such as Saudi Arabia (El‐Mouzan et al, 2007), China (Tian et al, 2020; Yang et al, 2015), Denmark (Nielsen et al, 2010; Tinggaard et al, 2014), and Canada (Park et al, 2017) have made their own national growth references and compared them to the WHO standards (2006), finding significant differences in the growth rates of children. This set of studies carried out in countries of diverse origins, phenotypic groups and genetic backgrounds leads us to believe that the WHO growth patterns might not be precise enough to estimate the number of malnourished individuals in different populations.…”
Section: Introductionmentioning
confidence: 99%